Community Empowerment in the Development of Halal Tourism in Religious Destinations of Syaikh Wasil Setono Gedong Kediri - Sofuan Jauhari; Mohammad Zakaria; Muhammad Khoirul Zuhdi Amrulloh; Mochammad Diky Wijayanto; Abdun Nafi; Abdul Hakim (TAAWUN, 2025)
This community service program aims to empower local communities around the religious destination of Syaikh Wasil, Setono Gedong, Kediri, in developing halal tourism through capacity building, improved understanding, and active community involvement. The program adopts the Asset-Based Community Development (ABCD) approach, focusing on identifying and activating local assets as the core strength of empowerment. Activities included public education on halal tourism concepts, entrepreneurship training based on Islamic principles, mentoring for Muslim-friendly tourism services, and the establishment of collaborative forums among local business actors and community groups. The results indicate increased community awareness of halal tourism principles, the emergence and strengthening of small businesses that align with sharia values, and collective initiatives to build the destination's image as a clean, friendly, and Islamic spiritual site. Additionally, the program has contributed to increased income for local micro-entrepreneurs and significantly improved visitor experiences. The benefit of this program lies in its ability to establish a sustainable, community-based halal tourism foundation, strengthen the local economy, and promote the cultural-religious identity of Setonogedong within an inclusive and value-added tourism framework.